Optimalisasi Sinergitas TNI-Polri Dalam Penanggulangan Terorisme di Indonesia - Boston Raymond Sihotang; Edi Susilo; Jumino Jumino (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2021)
This study aims to describe the synergy between TNI and Polri in countering terrorism. This research uses a mixed method with a SWOT analysis (Strength, Weakness, Opportunity, and Threat) to find the best strategies in increasing the synergy between TNI and Polri in countering terrorism. This research concludes that there is a need for a Presidential Decree which contains technical operational regulations so that the TNI's involvement mechanism is clearer in countering terrorism, command and control in countering acts of terrorism is one of the main factors that determine the success of operations. The ability of the TNI and Polri to cope with actions terrorism is still not optimal because of the lack of intensity of joint training in counterterrorism, as well as a narrow, negative and overblown understanding of